Synergistically Improving Mechanical and Interfacial Properties of Epoxy Resin and CFRP Composites by Introducing Graphene Oxide - Lijuan Cao; Jieying Zhi; Yu Yang; Liye Yuan; Yingjun Song; Xiaoxuan Lu; Chunxiang Lu (Advances in Polymer Technology)
In this study, graphene oxide (GO) was employed as nanoscale reinforcement for the development of high-performance carbon fiber reinforced plastic (CFRP) composites. Initially, epoxy resin was modified by incorporating GO with different weight proportion from 0.05 to 0.6 wt.%. Then the unidirectional CFRP composites were prepared with the modified epoxy resin by winding and compression molding technique. The optimized GO-CFRP composites with GO content of 0.1 wt.% present tensile strength of 2756 MPa and monofilament interfacial shear strength of 29.06 MPa, respectively, which are 14.4% and 12.5% higher than the corresponding values of the pristine CFRP composites. To intuitively observe the fracture process of the CFRP composites, the digital image correlation system was employed. It is verified that the moderate addition of GO can improve the stress concentration of the CFRP composites during the deformation process. In addition, the reinforcing mechanism is investigated by analyzing the fracture surface of the modified epoxy resin and the CFRP composites. The results indicate that GO can make the cracks deflect or bifurcate along with the epoxy resin which closes to graphene, resulting in synergistically improved mechanical and interfacial properties of the GO-modified CFRP composites.